2005
DOI: 10.1590/s0104-11692005000200008
|View full text |Cite
|
Sign up to set email alerts
|

A sinalização do enfermeiro entre os papéis de familiares visitantes e acompanhante de adulto e idoso

Abstract: This qualitative study was based on Symbolic Interactionism and Grounded Theory and aimed to understand the interactive experience of visiting family members and companions of hospitalized adult and elderly people and to develop a theoretical model of this experience. Data were collected through observations and interviews. Two phenomena emerged from the data analysis: living the expectation of hospitalization and assuming the roles of a family visitor or companion. Understanding this experience increased our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
20

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 4 publications
0
4
0
20
Order By: Relevance
“…Para o cuidador, além do cansaço físico e emocional decorrente da atividade de cuidar, também ocorre a perda da liberdade, pois há a necessidade de "abrir mão" de atividades sociais para prestar o cuidado. Ser cuidador de idoso dependente no domicílio é, na maioria das vezes, negligenciar sua própria vida, pois a prioridade é cuidar do familiar doente (18)(19) .…”
Section: (Cuidadora 7)unclassified
“…Para o cuidador, além do cansaço físico e emocional decorrente da atividade de cuidar, também ocorre a perda da liberdade, pois há a necessidade de "abrir mão" de atividades sociais para prestar o cuidado. Ser cuidador de idoso dependente no domicílio é, na maioria das vezes, negligenciar sua própria vida, pois a prioridade é cuidar do familiar doente (18)(19) .…”
Section: (Cuidadora 7)unclassified
“…The analysis demonstrated that, when a closer and therapeutic relation is established with the nursing team, the family companions start to consider and act in solidarity with the difficulties the institution itself imposes on the nursing work process (3) .…”
Section: Thismentioning
confidence: 99%
“…They do not manage to understand the challenges nurses and their team face in the realization of the work process in a broader sense (3) .…”
Section: Thismentioning
confidence: 99%
See 1 more Smart Citation
“…A partir daí, pude desenvolver algumas pesquisas que objetivaram compreender a experiência das famílias no contexto da doença mental (Silva, Moreno, 2004) e da hospitalização de adultos e idosos (Silva, Bocchi, 2005;Bocchi et al, 2007;Silva, Bocchi, Bousso, 2008), entretanto, a área da saúde coletiva, especificamente a Estratégia Saúde da Família (ESF) parecia-me muito propícia para aprofundar o conhecimento sobre família, pois acreditava que a família como unidade de cuidado era a perspectiva que dava todo o sentido ao processo de trabalho nesse cenário (Angelo, Bousso, 2001). …”
Section: Superando Os Desafios Para Acolher a Família E O Idosounclassified